Paired d18O and Sr/Ca, and reconstructed d18Osw records of Porites sp. from Rotuma (RO2) and Tonga (TNI2), Southwest Pacific - Sara Todorovic; Delphine Dissard; Braddock K Linsley; Henning Kuhnert; Henry C Wu (PANGAEA, 2024)
Two massive living Porites sp. coral colonies from Southwest Pacific were cored: from Rotuma, in 1998 (RO2), and from Tonga in 2004 (TNI2). TNI2 coral has previously published d18O time series (Linsley et al. 2008). Coral skeletal material was micro-sampled with a 0.5 mm drill bit, using a handheld Proxxon drill, in continuous 1 mm increments along the maximum growth axis to obtain close to monthly resolution. Samples were analyzed for d18O (RO2) and Sr/Ca (RO2, TNI2) allowing the reconstruction of d18Osw from both corals following the method of Ren et al. (2002). The trace element analysis of TNI2 was completed in every other mm resolution to match the resolution of Linsley et al. (2008). RO2 d18O was measured from individual skeletal powders at the MARUM, Germany, using a Thermo-Finnigan MAT 251 and MAT 253 gas isotope ratio mass spectrometer with Kiel I and Kiel IV automated carbonate preparation devices. Trace elements were measured at the Leibniz Centre for Tropical Marine Research, Germany on the Analytik Jena PlasmaQuant MS Elite Inductively Coupled Plasma Mass Spectrometer. Data was interpolated into monthly resolution using the ARAND software Ager and Timer (Howell et al., 2006), and is dating back to 1821 in Rotuma, and 1848 in Tonga. The coral proxy data of this dataset provides sea surface temperature and salinity reconstructions from the data poor regions of West Pacific Warm Pool and South Pacific Convergence Zone extending the sparse instrumental and gridded data products available.